"SAFE" LEVEL OF SOMATIC HEALTH IN INDICATORS REGULATION OF CARDIORESPIRATORY SYSTEM AT YOUNG MEN - Romanchuk, Alexander P; Guziy, Oksana; Podgorna, Viktoria; Glushchenko, Marina (Journal of Education, Health and Sport, 2015)
Romanchuk A. P., Guziy O. V., Podgorna V. V., Glushchenko M. M. «Безпечний» рівень соматичного здоров’я чоловіків молодого віку в показниках регуляції кардіореспіраторної системи = "Safe" level of somatic health in indicators regulation of cardiorespiratory system at young men. Journal of Education, Health and Sport. 2015;5(12):189-216. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35317 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A189-216 http://pbn.nauka.gov.pl/works/679228 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 25.11.2015. Accepted: 10.12.2015. «БЕЗПЕЧНИЙ» РІВЕНЬ СОМАТИЧНОГО ЗДОРОВ’Я ЧОЛОВІКІВ МОЛОДОГО ВІКУ В ПОКАЗНИКАХ РЕГУЛЯЦІЇ КАРДІОРЕСПІРАТОРНОЇ СИСТЕМИ "SAFE" LEVEL OF SOMATIC HEALTH IN INDICATORS REGULATION OF CARDIORESPIRATORY SYSTEM AT YOUNG MEN 1Romanchuk A. P., 2Guziy O. V., 1Podgorna V. V., 1Glushchenko M. M. 1Романчук О. П., 2Гузій О. В., 1Глущенко М. М., 1Подгорна В. В. 1South Ukrainian National Pedagogical University n.a. K.D. Ushinsky 2Lviv State University Physical Culture 1Південноукраїнський національний педагогічний університет ім. К.Д. Ушинського, м. Одеса 2Львівський державний університет фізичної культури, м. Львів "SAFE" LEVEL OF SOMATIC HEALTH IN INDICATORS REGULATION OF CARDIORESPIRATORY SYSTEM AT YOUNG MEN 1Romanchuk A.P., 2Guziy O.V., 1Podgorna V.V., 1Glushchenko M.M. 1South Ukrainian National Pedagogical University n.a. K.D. Ushinsky 2Lviv State University Physical Culture The aim of this study was to determine the functional state cardiorespiratory system in males younger with "safe" level of somatic health (LSH). Were examined 104 males aged 20,6 ± 0,9 years, engaged in various sports, and had no existing acute and chronic diseases. The survey was conducted using spiroarteriocardiorhythmography (SACR). It is shown that in all studied systems of regulation, regulation except SBP probably marked differences between persons with "safe" and "low" LSH. At the same time, the comparison of "safe" and "medium" LSH differences relate only to the predominance of sympathetic influences on heart rate, decrease suprasegmental effects on DBP, reducing regulatory influences on spontaneous breath and their high-frequency components, reducing of baroreflex sensitivity and cardiac output. Key words: "safe" level of somatic health, regulation of the cardiorespiratory system.